More large cardamom under Alnus trees - Gudade, B. A.; Chhetri, P.; Gupta, U.; Harsha, K. N. (Indian Horticulture, 2019)
Large cardamom-based agroforestry systems with Alnus nepalensis is most preferred in Sikkim Himalayan region. Large cardamom is benefited in mixed stands along with N2 fixing by Alnus nepalensis compared with stands containing only non-N2- fixing trees. Both Alnus nepalensis and large cardamom are native to the Himalayan region and the altitudinal range of Alnus nepalensis is sympatric with the agro- climatic range of large cardamom. The net primary productivity, yield, energy fixation rates, production and energy conversion are higher under Alnus nepalensis. To sustain Alnus-cardamom plantation, a rotational cycle of 15-20 years should be adopted. Besides some deterious effect of Alnus nepalensis on large cardamom if proper plantation management is done, it is advisable to use mixed stands along with N2 fixing by Alnus nepalensis instead of stands containing only non-N2- fixing trees.